INNOVATION OF ACCOUNTING LEARNING THROUGH MODEL ADDIE - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aims to: 1) developed a model of acounting learning through models of ADDIE learning processed. 2) developing learning media accounting in the form in learning cd.